Design of one non-linear adaptive control system and study of its tracking - Samiran Maiti; Achintya Das (Institute of Advanced Engineering and Science, 2019)
In this paper, an adaptive control method is proposed for a category of nonlinear systems. As the to begin with step in versatile controller plan, we select the control law which containing variable parameters. At that point select an adaption law for adjusting those parameters. We analyze the convergence properties and system stability using Lyapunov theory. The viability of the proposed approaches is appeared by implies of recreation on MATLAB.